Insights Into Halophilic Microbial Adaptation: Analysis of Integrons and Associated Genomic Structures and Characterization of a Nitrilase in Hypersaline Environments - Sonbol, Sarah (AUC Knowledge Fountain, 2021)
Hypersaline environments are extreme habitats that can be exploited as biotechnological resources. Here, we characterized a nitrilase (NitraS-ATII) isolated from Atlantis II Deep brine pool. It showed higher thermal stability and heavy metal tolerance compared to a closely related nitrilase. We also studied integrons in halophiles and hypersaline environments. Integrons are genetic platforms in which an integron integrase (IntI) mediates the excision and integration of gene cassettes at specific recombination sites. In order to search for integrons in halophiles and hypersaline metagenomes, we used a PCR-based approach, in addition to different bioinformatics tools, mainly IntegronFinder. We found that integrons and clusters of attC sites lacking a neighboring integron-integrase (CALINs) are abundant in halophilic bacterial genomes; and we detected archaeal integrons for the first time. Moreover, we found different classes of insertion sequences (ISs) within and nearby integrons and CALINs in halophilic genomes. We detected Group IIB introns for the first time associated with different integrons and CALINs. Finally, using 16S rRNA-based analysis, we assessed the prokaryotic diversity in two Egyptian hypersaline environments: Aghormy Lake in Siwa Oasis and Sebeaka saltern at the vicinity of Bardawil Lagoon. Both sites showed an abundance of family Rhodothermaceae, Bacteroidetes. Aghormy Lake showed abundance in Deinococcus-Thermus phylum known by its extremophilic members. The observed dissimilarities between both brines may reflect the differences in the biogeographical and physicochemical nature of the two sites. Our study may shed light towards a possible interplay of integrons with different associated MGEs in the adaptation of prokaryotes in hypersaline environments.